2022
DOI: 10.3389/fpsyt.2022.865226
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between the Recognition of Basic Emotions and Negative Symptoms in Individuals With Schizophrenia Spectrum Disorders – An Exploratory Study

Abstract: Current research suggests that emotion recognition is impaired in individuals affected by schizophrenia spectrum disorders (SSD). However, the specific impact of negative symptoms on the ability to recognize single basic emotions has not yet been explored sufficiently and is the aim of the present study. A sample of N = 66 individuals diagnosed with SSD was recruited at the Charité – Universitätsmedizin Berlin. In a first step, correlation analyses were conducted between seven different negative symptom subdom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 108 publications
0
1
0
Order By: Relevance
“…Studies have suggested that severe negative symptoms in psychosis ( 6 ) and greater illness severity ( 7 ) are associated with greater impairment in emotion recognition. Deficits do not appear to be associated with a higher polygenic risk score for schizophrenia, even though 1st degree relatives exhibit similar impairments ( 8 ), suggesting a separate genetic or familial pathway of social cognition impairments.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have suggested that severe negative symptoms in psychosis ( 6 ) and greater illness severity ( 7 ) are associated with greater impairment in emotion recognition. Deficits do not appear to be associated with a higher polygenic risk score for schizophrenia, even though 1st degree relatives exhibit similar impairments ( 8 ), suggesting a separate genetic or familial pathway of social cognition impairments.…”
Section: Introductionmentioning
confidence: 99%